Impact of cell shape in hierarchically structured plant surfaces on the attachment of male Colorado potato beetles (Leptinotarsa decemlineata) - Prüm, Bettina; Seidel, Robin; Bohn, Holger Florian; Speck, Thomas (Beilstein Journal of Nanotechnology, 2012)
Plant surfaces showing hierarchical structuring are frequently found in plant organs such as leaves, petals, fruits and stems. In our study we focus on the level of cell shape and on the level of superimposed microstructuring, leading to hierarchical surfaces if both levels are present. While it has been shown that epicuticular wax crystals and cuticular folds strongly reduce insect attachment, and that smooth papillate epidermal cells in petals improve the grip of pollinators, the impact of hierarchical surface structuring of plant surfaces possessing convex or papillate cells on insect attachment remains unclear. We performed traction experiments with male Colorado potato beetles on nine different plant surfaces with different structures. The selected plant surfaces showed epidermal cells with either tabular, convex or papillate cell shape, covered either with flat films of wax, epicuticular wax crystals or with cuticular folds. On surfaces possessing either superimposed wax crystals or cuticular folds we found traction forces to be almost one order of magnitude lower than on surfaces covered only with flat films of wax. Independent of superimposed microstructures we found that convex and papillate epidermal cell shapes slightly enhance the attachment ability of the beetles. Thus, in plant surfaces, cell shape and superimposed microstructuring yield contrary effects on the attachment of the Colorado potato beetle, with convex or papillate cells enhancing attachment and both wax crystals or cuticular folds reducing attachment. However, the overall magnitude of traction force mainly depends on the presence or absence of superimposed microstructuring.
Keywords: cuticular folds; epicuticular wax crystals; insect–plant interaction; papillae; structure–function relationship